TMIC-10. THE ROLE OF THE BRAIN MICROENVIRONMENT IN THE MIGRATION OF BREAST CANCER CELLS IN BRAIN METASTASES. (11th November 2019) - Kersch, Cymon; Muldoon, Leslie; Morris, DreeAnna; Neuwelt, Edward
Abstract: BACKGROUND: Breast cancer brain metastases have poor prognosis and few treatment options. When breast cancer cells invade the brain they interact with the vasculature and resident brain cells including microglia and astrocytes. We hypothesize that brain cells produce factors that enhance the growth and invasion of breast cancer cells in the brain. METHODS: Human breast cancer cell lines (MDA-MB231BR-HER2 and HCC1954) were inoculated intracranially in athymic rats as xenograft models of brain metastasis. Brains were analyzed for pro-tumorigenic factor expression in the tumor microenvironment using fluorescent immunohistochemistry. In vitro assays assessed factors involved in breast cancer cell proliferation, morphology, and migration. RESULTS: The tumor xenografts showed infiltration intothe perivascular space. Galectin-3 (Gal3), heparin-binding epidermal growth factor (HB-EGF), and Neuregulin (NRG1), factors known to interact with receptors expressed by breast cancer cells, co-localized with reactive microglia (Gal3) and astrocytes (HB-EGF and NRG1) in and around xenografts. In vitro, these factors individually increased HCC1954 cell proliferation and/or migration. In transwell co-culture assays, BV2 microglial cells increased the migration of HCC1954 cells >25 fold, which was prevented by cilengitide, an inhibitor of αvβ3-integrin cell adhesion protein. ELISA analysis demonstrated that BV2 microglia secrete Gal3 in the presence of HCC1954 cells. Gal3 is known to bind and induce clustering of αvβ3-integrin which is expressed on metastatic breast cancer cells. Immunohistochemistry of clinical specimens revealed that Gal3 is expressed in/around human breast cancer brain metastases. CONCLUSIONS: These data suggest that factors produced in the tumor microenvironment promote the growth and migration of breast cancer cells in the brain. Gal3, produced and secreted by activated microglia in vitro and expressed in and around brain metastases, increases the invasive capability of breast cancer cells. The interactions of neoplastic cells with the brain environment may provide a target to improve therapy of brain metastases.